2020
DOI: 10.1177/0960327120958102
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of small conductance calcium-activated potassium type-2 channel (SK2) delays occurrence of bupivacaine-induced cardiotoxicity in isolated mouse hearts

Abstract: Bupivacaine is frequently used for conducting regional anesthesia. When accidentally injected or excessively absorbed into circulation, bupivacaine can induce severe arrhythmia and potentially lead to cardiac arrest. The specific mechanisms underlying this cardiotoxicity, however, remain to be clarified. We transfected HEK-293 cells to express the small conductance calcium-activated potassium type-2 channel (SK2), and used a whole-cell patch clamp method in order to explore how bupivacaine affected these chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…10,11 Previous study has shown that bupivacaine could inhibit the SK2 current in a concentration-dependent manner in HEK293 cells. 15 After knocking out the SK2 channel gene, the toxicity of bupivacaine in an isolated mouse heart was significantly delayed. To verify the results, an in vivo mouse model was used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Previous study has shown that bupivacaine could inhibit the SK2 current in a concentration-dependent manner in HEK293 cells. 15 After knocking out the SK2 channel gene, the toxicity of bupivacaine in an isolated mouse heart was significantly delayed. To verify the results, an in vivo mouse model was used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the knockout of the SK2 channel gene could suppress the cardiotoxicity of bupivacaine in the isolated mouse heart. 15 However, this effect was not verified in vivo.…”
Section: Introductionmentioning
confidence: 95%